Improving the Control of Type I Error Rate in Assessing Differential Item Functioning for Hierarchical Generalized Linear Model When Impact Is Presented. (January 2014) - Chen, Jyun-Hong; Chen, Cheng-Te; Shih, Ching-Lin
Hierarchical generalized linear models (HGLMs) have been used to assess differential item functioning (DIF). For model identification, some literature assumed that the reference (majority) and focal (minority) groups have an equal mean ability so that all items in a test can be assessed for DIF. In reality, it is very unlikely that the two groups have an identical mean. If so, other model identification procedures should be adopted. A feasible procedure for model identification is to set an item that is the most likely to be DIF-free as a reference, so that the two groups can have different means and the other items can be assessed for DIF. In Simulation Study 1, several methods based on HGLMs in selecting DIF-free items were compared. In Simulation Study 2, those items assessed as DIF-free were anchored, and the other items were assessed for DIF. This new method was compared with the traditional method based on HGLMs in which the two groups are assumed to have an equal mean in terms of the Type I error rate and the power rate. The results showed that the new method outperformed the traditional method when the two groups did not have an equal mean.